2020
DOI: 10.1111/trf.15586
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a point‐of‐care method for screening blood donors for sickle cell status

Abstract: BACKGROUND Turbidity tests are commonly used for screening blood units for the presence of sickle cell trait (SCT) before transfusion to specific patient populations, based on recommendations of the AABB. In this pilot study, we evaluate a new method for screening blood donors and blood units for the presence of sickle hemoglobin. STUDY DESIGN AND METHODS This study was based at King Abdulaziz University Hospital in Jeddah, Saudi Arabia. Study participants were approached consecutively between July 24, 2016, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…This initial diagnosis was mainly made based on clinical features, especially the presence of VOC or anemia at the age of 2 years on average. These results are consistent with those of other African authors who reported an average age of around 10 years in SCD patients and a first diagnosis at the age of 2 years or later with VOC reported as the most frequent mode of first diagnosis [40][41][42][43][44][45]. A major barrier was the absence of large-scale early-life screening and the high cost of screening with conventional methods i.e.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This initial diagnosis was mainly made based on clinical features, especially the presence of VOC or anemia at the age of 2 years on average. These results are consistent with those of other African authors who reported an average age of around 10 years in SCD patients and a first diagnosis at the age of 2 years or later with VOC reported as the most frequent mode of first diagnosis [40][41][42][43][44][45]. A major barrier was the absence of large-scale early-life screening and the high cost of screening with conventional methods i.e.…”
Section: Discussionsupporting
confidence: 90%
“…To strengthen and improve the diagnosis of SCD in health centers located in remote areas of sub-Saharan Africa, it would be desirable to use a point of care test. This has already been successfully deployed in comparable environments and could potentially enable early screening of SCD [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The Emmel test cannot discriminate AS from SS, with a positive result in the both cases due to low-oxygen environment created under the coverslip during Emmel test. [21][22][23] Test Results TA B L E 1 Diagnostic evaluation in 160 patients followed for sickle-cell anemia With an incidence of AS in the adult population of 23.3%, 20 one can expect that blood donors may sometimes be AS. 21,24 This may result in an elevated level of AS-RBC, equally leading to false-positive Emmel test.…”
Section: Discussionmentioning
confidence: 99%
“…In AS heterozygotes, the low‐oxygen environment under the coverslip during the Emmel test, provokes the sickle shape also for AS‐red blood cells, resulting in a false‐positive test. The Emmel test cannot discriminate AS from SS, with a positive result in the both cases due to low‐oxygen environment created under the coverslip during Emmel test 21–23 . With an incidence of AS in the adult population of 23.3%, 20 one can expect that blood donors may sometimes be AS 21,24 .…”
Section: Discussionmentioning
confidence: 99%